CircCSPP1 Functions as a ceRNA to Promote Colorectal Carcinoma Cell EMT and Liver Metastasis by Upregulating COL1A1 - Wang, Qingyuan; Shi, Linsen; Shi, Kui; Yuan, Bo; Cao, Gang; Kong, Chenchen; Fu, Jun; Man, Zhongsong; Li, Xu; Zhang, Xuanfeng; Feng, Yifei; Jiang, Xinchun; et al. (Frontiers in Oncology, 2020)
The aberrant regulation of circular RNAs (circRNAs), ring structures formed by exon or intron back-splicing, has been identified as a novel characteristic of multiple cancers. However, the role of circRNAs in colorectal carcinoma remains to be elucidated. In the present study, we investigated the mRNA level and the promotional effect of circular RNA CSPP1 (circCSPP1) in colorectal carcinoma cell liver metastasis. By bioinformatic analysis of 10 paired samples of colorectal carcinoma, we identified circCSPP1 as a significantly upregulated circular RNA in colorectal carcinoma tissues, and its upregulation was correlated with higher M stage. The gain- and loss-of-function assays revealed that circCSPP1 promotes the migration and invasion of colorectal carcinoma cells in vitro and in vivo. Mechanistically, similar miRNA response elements are shared between circCSPP1 and COL1A1. We demonstrated that circCSPP1 upregulates the mRNA levels of COL1A1, which plays a pivotal role in the process of epithelial-mesenchymal transition (EMT), by competitively binding to miR-193a-5p and preventing miR-193a-5p from decreasing the expression of COL1A1. In conclusion, this finding indicates that circular RNA circCSPP1 may act as a promising therapeutic target by regulating the EMT process in colorectal carcinoma via activation of the circCSPP1/miR-193a-5p/COL1A1 axis.